Penafsiran Isma’il Haqqi Terhadap Tokoh Anonim dalam Surah Zahrawain: Studi Kitab Tafsir Ruh Al-Bayan - Safitri, Lidia; Rohman, Abdur; Ubet, Abdulloh (JOM, 2025)
Anonymity is often associated with identity protection, but it can also encourage irresponsible actions, such as the spread of hoaxes. Interestingly, the concept of anonymity is not only found on social media but also in various Quranic narratives. This study aims to analyze the forms, patterns, and motives of anonymity in anonymous stories within Surah Zahrawain as interpreted in Tafsir Ruh Al-Bayan by Isma‘il Haqqi, as well as to examine its relevance in contemporary human life. This research employs a qualitative method with a textual analysis approach to tafsir (Quranic exegesis). Data were collected from Tafsir Ruh Al-Bayan and analyzed descriptively to identify the forms and motives of anonymity in Quranic narratives. The results indicate that there are 32 anonymous figures in 23 stories in Surah Zahrawain, including Hawa’ (Eve), ‘Amil bin Sharohil, and King Titus. The motives behind anonymity in these narratives include protecting a character’s identity due to their deviant actions, simplifying expressions, and facilitating pronunciation. This study contributes by providing a new understanding of the role of anonymity in Quranic narratives, which not only serves to obscure identities but also reflects values of politeness and alignment with normative ethics in society.